Errors and Barriers Among Islamic Religious Education Students with Low Numeracy Literacy in Solving Zakat Problems - Chintia Putri Wulandari; Lovi Leoni (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2026)
This study aims to describe the errors and barriers encountered by Islamic Religious Education (PAI) students with low numeracy literacy in solving zakat problems, as examined through numeracy literacy indicators. A qualitative descriptive design was employed. The participants were PAI students at UIN Sulthan Thaha Saifuddin Jambi, selected purposively based on the results of a numeracy literacy diagnostic test. Data were obtained from a written zakat-context test, observations of the problem-solving process, and semi-structured interviews. The data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that, although students generally understand the zakat context, they experience barriers in several key numeracy literacy indicators: (1) interpreting quantitative information, (2) reasoning and modeling relationships among variables, (3) performing calculations in a systematic and structured manner, and (4) evaluating and reflecting on the reasonableness and completeness of the results. The dominant errors include neglecting nisab as a numerical decision threshold, selecting inappropriate data and operations, and producing incomplete solutions. These results suggest that efforts to strengthen zakat instruction should prioritize the comprehensive development of numeracy literacy, rather than focusing solely on computational proficiency.